(untitled) (Development Service Industry Management, 2025)
The article examines the management of leisure potential in the cruise tourism system as a key factor in the development of the service economy in the context of the global transformation of the tourism market. The socio-cultural, psychological and organizational aspects of leisure interaction of tourists are revealed, its role in the formation of a value-oriented travel experience is determined. It is substantiated that effective management of leisure processes ensures the integration of the principles of sustainable development, inclusion and digitalization, which allows to increase the competitiveness of cruise companies and the quality of tourist service. An analytical model of the relationship between socio-cultural and psychological determinants of tourists’ leisure activity is proposed, which forms the basis for improving management decisions in the field of recreational management. Promising directions for the development of cruise tourism in the context of a green and inclusive economy are identified, which combine technological innovations, humanistic values ​​and a responsible attitude to the environment.